Distribution and community structure of chloropid flies (Diptera: Chloropidae) in Nearctic glacial and post‐glacial grasslands. Issue 4 (21st June 2016) - Solecki, Anna M.; Buddle, Christopher M.; Wheeler, Terry A.
Abstract: Arthropod species inhabiting disjunct xeric grasslands in the Yukon Territory, Canada may be relicts of Pleistocene steppe assemblages widespread in Beringia during glaciation, or they may be recent remnants of northward expansion of southern grassland communities during the early‐Holocene Hypsithermal. To assess the likely origin of the Yukon grassland arthropod community, grassland‐associated Chloropidae (Diptera) were compared from three regions: the Canadian Prairies, the Peace River region of Alberta and the southern Yukon. If Yukon grassland insect communities, like those in the Peace region, result primarily from northward dispersal during the Hypsithermal, chloropid assemblages in all regions would be similar, except that species richness would decline with increasing latitude. If, however, they are primarily relicts of Pleistocene steppe communities, Yukon chloropid assemblages would be distinct from southern assemblages. There was a latitudinal gradient of decreasing species richness and Yukon assemblages were distinct from Prairie and Peace region assemblages, based on cluster analysis, non‐metric multidimensional scaling and pairwise comparisons of Morisita similarity indices. Community‐level analyses suggest that Yukon assemblages have been separated from those in the Prairies and Peace regions since before the Hypsithermal and likely contain a mix of relict populations inhabiting Pleistocene steppe remnants in East Beringia with recent northward post‐glacial dispersal from the southern Prairies. Dispersal from eastern Russia via Beringia appears to have been negligible.